The influence of workload and health behavior on job satisfaction of general practitioners - Götz, Katja; Musselmann, Berthold; Szecsenyi, Joachim; Joos, Stefanie (Family Medicine, 2013)
Workload, personal health behavior, and job satisfaction of the physicians are crucial aspects for the quality of care they provide. The aim of our study was to identify influencing factors on job satisfaction with regard to general practitioners' (GPs) characteristics such as age, gender, health behavior, body mass index (BMI), and workload. - A cross-sectional survey with a sample of 1,027 German GPs was used. Job satisfaction was measured according to a modified version of the Warr-Cook-Wall job satisfaction scale. Further, we collected data about health behavior and BMI of GPs and demographic data. Group comparison was evaluated using ANOVA with Bonferroni correction for post-hoc tests. A linear regression analysis was performed in which each of the job satisfaction items were handled as a dependent variable. - The response rate was 34.0%. GPs were rather satisfied with their job with the exception of "hours of work," "physical working condition," and "income." GPs working in cities had less working hours per week, less number of patients per day, longer consultation times, and a higher proportion of privately insured patients compared to GPs working in rural areas. Being female, a higher age, a good health behavior, a lower BMI, and a high proportion of privately insured patients were positively associated with job satisfaction. - Our results suggest that job satisfaction depends on different aspects of working conditions and individual characteristics. Therefore, strategies to improve job satisfaction should target improving working conditions and activating physicians' health resources.
Gesehen am 11.02.2020